PERAN GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA SD NEGERI 26 AMPENAN: PERAN GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA SD NEGERI 26 AMPENAN - Nimadetriandani, Ni Made Triandani; Novyastini, Ni Ketut; Pramana, Ida Bagus Kade Yoga (UPADHYAYA: JURNAL PENELITIAN PENDIDIKAN, 2025)
The role of teachers in education increases interest in learning which includes efforts to create a learning environment that inspires students to enjoy learning. Interested learning is self-directed, including enthusiasm, seriousness, concentration, and strategies to achieve goals. Educators need to improve the quality of learning in the classroom, the quality of learning in the classroom can be improved in various ways, so that students feel comfortable. This research uses a qualitative descriptive method to describe and analyze in detail the role of teachers in developing students' interest in learning. The results of this research are also based on observations made by researchers at SDN 26 Ampenan. To increase the effectiveness, efficiency and quality of learning so that it meets expectations, in the learning process teachers are encouraged to carry out various innovations such as by creating learning media, especially in subjects that are considered difficult, students will be more interested in achieving their academic potential effectively maximum. Keywords: The Role of Teachers, Interest in Learning